MASSIFICATION AT HIGHER EDUCATION INSTITUTIONS; CHALLENGES ASSOCIATED WITH TEACHING LARGE CLASSES AND HOW IT IMPACTS THE QUALITY OF TEACHING AND LEARNING - Taurayi Stephen Nyagope (STAI Ma'had Aly Al-Hikam Malang, 2023)
The paper engages with the phenomenon of large classes in higher education institutions in South Africa and its challenges to the quality of teaching learning. Most public higher education institutions in South Africa, in response to historical conditions, have enrolled students more than their capacity, resulting in massification and negative consequences on educational quality. There has been a plethora of literature on the teaching of large classes, however, few studies offer a comprehensive engagement on the challenges presented by teaching larges and its impact on quality of education as well as innovative strategies that can be used to teach and different learning pedagogies that can be used. This essay identified the challenges of teaching large class in higher education institutions due to massification and large enrolments and their implications on sustaining and enhancing quality of teaching and learning. In addition, I suggested several strategies that can be used to overcome the challenges of teaching large classes as well as how to monitor and evaluate these strategies with the aim of improving quality of higher education in the era of massification. Accordingly, the human capital theory was adopted. Furthermore, a qualitative research approach was applied in this study and a systematic literature review was used to collect and review information according to the guiding principles of the hermeneutic framework. The essay contributes to literature with the strategies to enhance quality of teaching and learning, student engagements and teaching approaches aimed at reaching all students in large classes.